Regulatory effect of Phikud Navakot extract on HMG-CoA reductase and LDL-R: Potential and alternate agents for lowering blood cholesterol - Napatara Tirawanchai (2019)
© 2018 The Author(s). Background: For decades, various cardiovascular symptoms have been relieved by the use of Ya-Hom Navakot, which is a formulation comprising 54 herbal medicines. The Thailand Ministry of Public Health listed Ya-Hom Navakot's nine active principle and nomenclative herbal ingredients and termed them 'Phikud Navakot' (PN). Several reports have confirmed that PN has cardiovascular benefits similar to Ya-Hom Navakot. However, whether PN facilitates lipid-lowering activity remains unclear. Methods: The present study investigated an in vitro model for examining the gene expression levels of 3-hydroxyl-3-methylglutaryl-CoA reductase (HMGCR) and low-density lipoprotein receptor (LDL-R) in HepG2 cells using qRT-PCR. The ethanol and water extractions of Ya-Hom Navakot, PN and Ya-Hom Navakot without PN were compared. Results: One mg/ml of both NYEF and NYWF were found to significantly lower cholesterol by either the up-regulation of LDL-R or down-regulation of HMGCR compared with negative controls and 1 mg/ml simvastatin (p < 0.05). PNEF also up-regulated LDL-R gene expression, even more than NYEF (p < 0.05). In addition, the ethanol and water extracts of PN significantly down-regulated HMGCR gene expression compared with those of Ya-Hom Navakot without PN (p < 0.05). Conclusion: The use of Ya-Hom Navakot or PN may provide an alternative treatment to lower cholesterol through HMGCR gene inhibition and LDL-R gene enhancement.